Mutual HIV Status Disclosure is Associated with Consistent Condom Use in Public Sector ART Clients in Free State Province, South Africa : A Short Report - Booysen, Frederik le Roux; Wouters, Edwin; de Walque, Damien; Over, Mead (Taylor and Francis, 2017)
Risky sexual behavior in PLWHA on antiretroviral therapy threatens both prevention and treatment efforts, but disclosure promises to support safer sexual practices. This paper investigates the association between HIV self-disclosure and consistent condom use in a cohort of public sector patients on antiretroviral (ARV) treatment. Using data from the FEATS cohort study, logistic regression analysis shows that knowledge of your partner’s HIV status is positively associated with consistent condom use (OR 2.73, 95% CI 1.37–5.43, p = 0.004) and so too mutual HIV disclosure (OR 3.38, 95% CI 1.60–7.18, p = 0.001). Prevention and treatment programs, through couple HIV counselling and testing (CHCT) and other assistance programs, should focus on supporting the mutual disclosure of HIV status among PLWHA on ARV treatment.